Bilateralism in services trade : is there fire behind the (BIT-)smoke? - Adlung, Rudolf (WTO GenevaCH, 2008)
Focuses on bilateral investment treaties which have been signed as stand-alone instruments. Pays attention to their interaction with potentially relevant GATS provisions, in particular the MFN requirement pursuant to Article II.